1996
DOI: 10.1128/iai.64.7.2371-2380.1996
|View full text |Cite
|
Sign up to set email alerts
|

Bacterially induced bone destruction: mechanisms and misconceptions

Abstract: Normal bone remodelling requires the coordinated regulation of the genesis and activity of osteoblast and osteoclast lineages. Any interference with these integrated cellular systems can result in dysregulation of remodelling with the consequent loss of bone matrix. Bacteria are important causes of bone pathology in common conditions such as periodontitis, dental cysts, bacterial arthritis, and osteomyelitis. It is now established that many of the bacteria implicated in bone diseases contain or produce molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
272
0
16

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(293 citation statements)
references
References 111 publications
5
272
0
16
Order By: Relevance
“…E. coli LPS was preferred compared with other oral flora-related bacterial LPS as it is easily accessible and it is still relevant for oral cavity. 31 Baseline LPS contamination is a commonly reported problem related to similar in vitro study models as LPS can be easily found in the surrounding environment. Most of the published in vitro studies report several cycles of autoclaving and/or chemical processing to remove this type of baseline LPS prior to the actual experiment.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli LPS was preferred compared with other oral flora-related bacterial LPS as it is easily accessible and it is still relevant for oral cavity. 31 Baseline LPS contamination is a commonly reported problem related to similar in vitro study models as LPS can be easily found in the surrounding environment. Most of the published in vitro studies report several cycles of autoclaving and/or chemical processing to remove this type of baseline LPS prior to the actual experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterially induced osteoclastogenesis is not without precedent (see review by Nair et al, 1996). Multinucleation and TRAP production by spleen cells has been reported following treatment with Porphyromonas gingivalis, a periodontal pathogen, or lipopolysaccharide from E. coli (Abu-Amer et al, 1997;Jiang et al, 2002), and the addition of surface-associated material from P. gingivalis, Actinobacillus actinomycetemcomitans, or Staphylococcus aureus to bone marrow cultures reportedly causes multinucleation and bone resorption in vitro (Wilson et al, 1986;Wilson et al, 1993;Nair et al, 1995), although this effect may be due to an increase in RANKL by associated osteoblasts, rather than a direct effect on osteoclast precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclast-like cells have been observed following bacterial treatment, albeit after long incubation times (Nair et al, 1996;Abu-Amer et al, 1997). As B. pseudomallei and Burkholderia thailandensis induce MNGC formation, and osteoclasts are MNGCs, we investigated whether any similarity exists between osteoclasts and B. pseudomallei-induced or B. thailandensis-induced MNGCs.…”
Section: Introductionmentioning
confidence: 99%
“…15 Over the past decade, there has been considerable evidence that microorganisms may be implicated in bone loss and osteoporosis. 16 For that, during osteoporotic bone grafting, the infection is still one of the most serious complications in implant surgeries. Specifically, Staphylococcus aureus and Brucella are known to infect, survive within human osteoblastic cells and secrete cytokines such as tumour necrosis factor (TNF)-α and interleukin (IL)-1ß.…”
Section: Introductionmentioning
confidence: 99%